Murree Clay Problems and Water-Based Drilling Mud Optimization: A Case Study from the Kohat Basin in Northwestern Pakistan - Qadri, S.M.T. (MDPI, 2022)
Drilling fluids with subtle filtration and rheological characteristics are essential to optimize the functioning of oil and gas well drills. The Early Miocene Murree Formation in the Kohat Basin of Pakistan is generally referred to as the Murree Clays. When mixed with water-base drilling mud, ultra-fine particles of the Murree Formation tend to eradicate default fluid rheological properties and result in wellbore instabilities during drilling in that area. To obtain the optimized mud to deliver the drilling operation efficiently, we aimed to mitigate the impact of Murree clay on the drilling mud. We analyzed the drilling mud to observe the effects of the mud additive on clays on the basis of the samples from the Murree Clays. On the basis of the experimental tests, we observed that the rheological properties of mud significantly improved in the presence of KCl. KCl prevented the smectite group swelling inclinations and reduced rheological values to 25, 33.3, 48.6, and 65.2. The plastic viscosity increased as the concentration of clays increased; however, there was a noticeable reduction in the yield point values with the introduction of KCl. The laboratory results showed that Mud + 4 Clay + 1 KCl proved to be the best mitigation while preserving the rheological and performance characteristics of the mud. Tests enabled the scope to increase the inhibition efficiency and optimize customization. Depending on the clay present in the Murree formation, drilling fluid optimization is proposed to reduce mud-related drilling problems in this area. Copyright: Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.